Leader II -yhteisöaloite keinona maaseutualueiden kehittämisessä - Viljanen, Kirsi (Maatalouden taloudellinen tutkimuslaitos, 1997)
In addition to Objectives 1, 5b, and 6, the EU is making an attempt to promote the vitality of the rural areas by means of LEADER II Community Initiative, which is specifically aimed at the development of the rural areas. In LEADER I programme implemented in 1991-1993, a new approach to the development of the countryside was tested as the local residents were given the opportunity to contribute to the improvement of their own living conditions. In LEADER, funds from both the EU and national sources were directed to the implementation of the development programmes prepared by local work groups. It was considered important to continue LEADER I programme, and activities based on the principles of LEADER will be continued through LEADER II programme. This paper is concerned with the implementation of LEADER II Community Initiative in Finland and the role of the different authorities in the implementation. The contents of the projects and views of the local parties on the development needs of the rural areas are covered. The results hopefully help the future allocation of funds of the LEADER programme. The study is based on a master s thesis prepared at the Department of Economics and Management of the University of Helsinki, in which the main research topic was to find out how well the own initiative of the local residents is being realised in the Finnish LEADER II.
Leader community initiative as means of rural development
Artikkeli perustuu HY:n taloustieteen laitoksella esitettyyn pro gradu -tutkielmaan maatalouspolitiikan oppiaineessa. Tutkimuksen ohjasi professori Jukka Kola
Keywords: Ma; maaseutualueiden kehittäminen; aluesuunnittelu; regional development; regional planning; rural areas